The Effectiveness of the Health Insurance Program in Improving Access to Health Services for Beneficiaries of Contribution Assistance: A Review - Andi Isnaeni; Ramadhan Tosepu; Ruslan; Nani Yuniar; Mubarak; Asnia Zainuddin (Journal of Health Science and Pharmacy, 2025)
Background: Equitable access to healthcare services is widely recognized as a fundamental human right and a central objective of health system development, including in Indonesia. Despite this commitment, economically disadvantaged populations continue to face significant barriers to healthcare access, including financial constraints, disparities in service quality, and unequal distribution of health infrastructure. In response, the Indonesian government introduced the National Health Insurance program (Jaminan Kesehatan Nasional/JKN) to reduce financial barriers and expand access to essential healthcare services for poor and vulnerable populations. Objectives: This study aims to analyze the effectiveness of the JKN program, together with comparable health insurance schemes in other countries, in improving access to healthcare services among poor populations, while identifying supporting factors. Methods: A Systematic Literature Review was conducted following PRISMA guidelines. Relevant studies were identified through electronic databases, including Google Scholar, PubMed, Scopus, and ScienceDirect, using keywords related to health insurance, healthcare access, poor populations, program effectiveness, and health policy. Results: The indicate that JKN has increased healthcare utilization among poor households by reducing out-of-pocket expenditures and improving access to primary and referral services. Digital innovations, such as the JKN Mobile application, enhance efficiency but are limited by digital literacy gaps. Evidence from Laos and Rwanda shows similar improvements. Conclusion:  health insurance programs such as JKN expand healthcare access for poor populations; however, sustainability depends on health system readiness, equitable resource distribution, service quality, and policy support.